Bean production and soil chemical properties are affected by the application of different residue levels from three crop rotations. Issue 9 (29th July 2022) - Hirzel, Juan; Undurraga, Pablo; León, Lorenzo; Carrasco, Jorge; González, Jorge; Matus, Iván
ABSTRACT: Crop rotations and residue management contribute to the sustainability of the soil and environment and reduction of fertiliser use. However, appropriate crop and residue level combinations have yet to be determined to maximise productivity, while ensuring the preservation of soil resources in different agricultural production systems. The experiment evaluated production and soil chemical properties in bean after three preceding crops (bread wheat, durum wheat, and corn) with four residue incorporation levels (0%, 50%, 100%, and 200%) under irrigation conditions in volcanic soil in south-central Chile. A split plot design with four replicates was used. Results indicated that the production of grain and crop residue of bean were higher after corn and durum wheat. The preceding crop also affected some soil chemical properties, especially after the corn crop. The production parameters were not affected by the different residue levels; these had a positive effect on the concentrations of N, K, and Mg and an effect that was directly proportional to the residue level being used. Correlations between soil chemical properties were also established, consistently highlighting the increase in the concentration of the nutrients N, K, Ca, and Mg associated with increases in organic matter content.